2004
DOI: 10.1016/s0093-934x(03)00443-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring syllable boundaries during speech production

Abstract: This study investigated the encoding of syllable boundary information during speech production in Dutch. Based on LeveltÕs model of phonological encoding, we hypothesized segments and syllable boundaries to be encoded in an incremental way. In a selfmonitoring experiment, decisions about the syllable affiliation (first or second syllable) of a pre-specified consonant, which was the third phoneme in a word, were required (e.g., ka.No ÔcanoeÕ vs. kaN.sel ÔpulpitÕ; capital letters indicate pivotal consonants, dot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Therefore, participants might have pressed the YESbutton to all pictures they were familiar with and the NO-button to everything else, whether real object or not (i.e., there was no need to identify the objects). To show that this was not the case we refer to an object/non-object identification experiment that was done as a control experiment in another study (Jansma & Schiller, 2004). In that study, participants were once exposed to a set of existing objects and non-objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, participants might have pressed the YESbutton to all pictures they were familiar with and the NO-button to everything else, whether real object or not (i.e., there was no need to identify the objects). To show that this was not the case we refer to an object/non-object identification experiment that was done as a control experiment in another study (Jansma & Schiller, 2004). In that study, participants were once exposed to a set of existing objects and non-objects.…”
Section: Discussionmentioning
confidence: 99%
“…(The pictures of objects and non-objects used in the current experiment formed a subset of the materials used in the Jansma and Schiller study.) Participants were then required to make the object/non-object decision, and it turned out that even under circumstances in which participants did not have prior practice with the pictures there was no difference in RTs between pictures corresponding to picture names with first syllable stress and those with second syllable stress (see Jansma & Schiller, 2004, for details).…”
Section: Discussionmentioning
confidence: 99%
“…phoneme detection or go/no-go tasks (e.g. Jansma and Schiller, 2004;Schiller, 2006;Schmitt et al, 2000Schmitt et al, , 2001). An interesting solution to the second issue emerges from work by Zwitserlood et al (2000), especially with regard to morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these findings about syntactic representations, recent evidence from our own laboratory as well as from other laboratories demonstrated that self-monitoring does occur at the level of phonological encoding. We have empirical data about the monitoring of phonological segments (Schiller, in press;Wheeldon & Morgan 2002), word stress (Schiller 2001; Schiller et al, in press), syllable boundaries ( Jansma & Schiller 2004), and syllables (Morgan & Wheeldon 2003). However, we also have evidence that participants are unlikely to monitor a phoneticacoustic representation of the respective utterances.…”
mentioning
confidence: 99%